Behandlung der Wortbildungselemente in deutsch-tschechischen Übersetzungswörterbüchern - Šemelík, Martin (Linguistik Online, 2014)
in the emerging Large German-Czech Academic Dictionary, an output of a project pursued at the Institute of Germanic Studies, Faculty of Philosophy & Arts, Charles University in Prague. It is shown how contrastive analysis can be supplemented by a corpus-based view using new corpus-linguistic tools.